Perlindungan Hukum Terhadap Pembeli Atas Peralihan Saham Yang Tidak Mendapatkan Persetujuan Dari Menteri Energi Dan Sumber Daya Mineral Republik Indonesia - Elida Marbun; Ramlani Lina Sinaulan; Yurisa Martanti (JOURNAL of LEGAL RESEARCH, 2022)
Article 64 paragraph (1) of the Regulation of the Minister of Energy and Mineral Resources of the Republic of Indonesia Number 7 of 2020 states that if the holder of an IUP or IUPK wishes to make changes to its shares, it must first obtain the approval of the Minister or the Governor in accordance with their authority before registering with the Indonesian ministry in charge of government administration. the practice of law In actuality, however, the buyer has paid the seller in full for the shares under the Sale and Purchase of Shares Agreement, and it turns out that the seller cannot obtain approval from the Minister of Energy and Mineral Resources of the Republic of Indonesia. This is a normative legal study employing a statute, case, conceptual, and analytic method. According to the results of the study, the transfer of shares that does not receive approval from the Minister of Energy and Mineral Resources of the Republic of Indonesia cannot be continued with the signing of the transfer of rights to shares because the objective requirements cannot be met. This is due to the fact that shareholders of a limited liability company holding an IUP are required to get prior approval from the Minister of Energy and Mineral Resources of the Republic of Indonesia. In order for the disapproval of the change in shares to render the Sale and Purchase of Shares invalid.